Influence of Presintering Parameters on the Mechanical Properties of Presintered Dental Zirconia Block - Amat, Noor Faeizah Faeizah; Raji, Shari Lawuo; Muchtar, Andanasuti; Amril, Muhammad Sufiyan; Ghazali, Mariyam Jameelah; Yahaya, Norziha (International Journal of Integrated Engineering, 2018)
This study aimed to investigate the effects of presintering parameters on the mechanical and microstructural properties of presintered zirconia block. The zirconia block was prepared using colloidal and cold isostatic pressing techniques and subsequently subjected to various presintering procedures at 850 °C, 900 °C, and 950 °C with two different heating rates (3 and 10 °C/min). All samples were evaluated in terms of hardness, density, and morphology. Results showed that the sample porosity decreased with increment in the presintering temperature. On the contrary, the Vickers hardness increased from 1.8 GPa at 850 °C to 2.7 GPa at 950 °C at 10 °C/min heating rate. The sintering temperature of 950 °C with 3 °C/min heating rate was considered the most suitable parameter among presintering procedures, with high theoretical density (96.2%) and appropriate hardness (1.27 GPa) that are within the range of commercial zirconia block hardness values for restoration milling procedure. Furthermore, to sinter the block samples successfully without considerable failure, the heating and cooling rates should be lowered to ≤3 °C/min. Therefore, on the basis of these results, the forming methods and the sintering temperature influence the resultant mechanical and microstructural properties of the final sample.